THE INFLUENCE OF COOPERATIVE LEARNING MODEL WITH THE ASSISTANCE OF AUDIO-VISUAL MEDIA - Reni Anggreani; Khairuna Khairuna (TA'DIB: JURNAL PENDIDIKAN ISLAM, 2022)
The use of inappropriate learning models and learning media can affect student learning outcomes, by carrying out conventional learning which tends to be teacher centered so that students become passive and have low learning outcomes, it is necessary to make learning efforts involving teacher and student interaction, then by using cooperative learning models assisted by audio-visual media is expected to have a good influence on student biology learning outcomes. This research was conducted from March to May 2022. This study used a quantitative approach with a Quasi Experiment Design research design in the Nonequivalent Control Group Design, namely an experimental design by looking at the differences in pre-test and post-test between the experimental group and the control group, the test instrument was pre-test and post-test. This study has a sample of class XI MIA – 3 as the experimental class and XI MIA - 4 as a control. The average result of the experimental post-test was 96.3 and the average post-test control was 85.7. So that the experimental class has added value for the better and there is an influence on the application of cooperative learning models assisted by audio-visual media on biology learning outcomes for class XI students on the subject of the human excretory system at MAN 1 Medan. With the ttest test of the Experimental Class and Control Class, it has been obtained that tcount is 4.004 and ttable is 1.672, so that it shows tcount > ttable, then Ha is accepted and Ho is rejected.